The improvement of beef cattle through breeding methods. - Smith, W.H.; Holland, L.A.; Ibsen, H.L. (Kansas Agricultural Experiment Station, 2012)
The purebred Shorthorn cattle breeding project has proceeded according to plan this year. The project was planned to facilitate the collection of production data which will be used to devise testing and breeding procedures useful to cattlemen for the improvement of cattle. Pedigree barriers were established in the original College herd for the development of two inbred lines. College Premier 29th, 2368167, and Gregg Farms Hoarfrost, 2492499, have been used as herd sires for this purpose and the inbred lines have been designated as the Wernacre Premier and Mercury lines for these respective sires. An inbreeding program was initiated for the Wernacre Premier line in 1949 and the first inbred calves were produced in 1950. Calves representing the second generation of inbreeding were produced in 1952. The inbreeding program for the Mercury line was initiated in 1952 and the first in bred calves for this line will be produced in 1953.
Keywords: Beef; Breeding; Calf crop